Economic Inequality in Central, East and Southeast Europe - Sebastian Leitner; Mario Holzner (Intervention. European Journal of Economics and Economic Policies, 2008)
The article analyses the issue of economic inequality in the transition economies of Central, East and Southeast Europe. It consists of a literature review and a descriptive analysis as well as an econometric modelling exercise. In the first part we point at the fact that the rise in income inequality was triggered by the magnitude of transitional output loss and a reduction of formal employment. Rising wage inequality was at the core of total income dispersion, while government transfers had a redistributional function only in Central and Southeast European countries contrary to the Commonwealth of Independent States (CIS). In the econometric analysis it is found that for instance public utilities infrastructure liberalisation has increased inequality in transition, while price and trade liberalisation has decreased it. A high share of employment in industry and high government expenditures are connected with less inequality.
Keywords: D63; O15; P36; 330; income distribution; inequality; transition economies